“Since When Is Steve Urkel White?” – Vocal Blackface In The German Dubbing Landscape - Patrick Ploschnitzki (Studies in 20th & 21st Century Literature, 2023)
Dubbed (i.e., lip-synchronized audiovisual translation of) movies and television are ubiquitous in German-speaking countries and often consumed without active reflection of their production. Due to this inattention, the domestication / replacement of cultural references in US media translated into German often goes unnoticed. Translational decision-making becomes highly problematic, however, when entire cultures are replaced or disregarded as a result. In 2004, applied linguist Robin Queen demonstrated that Black actors were dubbed by white voice actors with German dialects and sociolects traditionally read as “blue collar.” There has not been any follow-up research to her crucial contribution that remains topical: the (re-)presentation of Black Germans and other minoritized voices in German media is still based on colonial and other racist stereotypes, which are in turn reinforced through popular culture in dubbing. In the United States, pop-cultural monoliths such as "The Simpsons" and "Family Guy" reluctantly recast voice actors for characters of Color after having come under pressure by discussions surrounding the Black Lives Matter movement and documentaries such as Hari Kondabolu’s “The Problem with Apu.” Following up on Queen’s work, this article provides accessible, up-to-date data and a snapshot of the current practice of casting white voice actors for characters of Color in US popular culture dubbed into German for German-speaking markets, defined here as “vocal blackface.” This research shows that these casting choices have been and remain in place largely without criticism by means of a close reading of publicly available German voice actor casting online database. The article provides the foundation to identify structural and societal reasons why recastings are not (yet?) happening in Germany.
Keywords: dubbing; German; audiovisual translation studies; translation; cultural studies; media studies; whitewashing; applied linguistics